The influence of prestroke proficiency on poststroke lexical-semantic performance in bilingual aphasia - Peñaloza, Claudia (Aphasiology, 2019)
BACKGROUND: Bilingual persons with aphasia (BWA) may present different degrees and patterns of impairment in their two languages. Previous research suggests that prestroke proficiency may be amongst the factors determining poststroke language impairment in BWA, however this relationship is not well understood. AIMS: The purpose of this study was to examine the relationship between prestroke proficiency and poststroke lexical-semantic performance in BWA and to identify common patterns of language impairment in this population. METHODS AND PROCEDURES: Twenty-seven Spanish-English BWA (14 female, age range = 29–88 years) were administered a language use questionnaire (LUQ) to measure several aspects of their bilingual language history that contribute to their prestroke proficiency in both languages. They also underwent standardized language assessments tapping lexical-semantic performance in each language. A principal component analysis was first conducted on the LUQ metrics to determine the factors that contributed to prestroke proficiency in each language. Next, regression analyses allowed assessing the relationships between prestroke proficiency and poststroke lexical-semantic performance in both languages. Differences in proficiency and language performance across languages were contrasted prior and after stroke to identify profiles of impairment. OUTCOMES AND RESULTS: Prestroke proficiency in the native language was determined by daily use, educational history, lifetime exposure, and language ability rating. Prestroke proficiency in the second language was determined by age of acquisition, daily use, educational history, lifetime exposure, lifetime confidence, family proficiency, and language ability rating. Prestroke proficiency significantly predicted poststroke lexical-semantic performance in BWA in both languages. Twenty-two participants presented parallel impairment while only three presented differential impairment. CONCLUSIONS: Our results confirm that prestroke language proficiency is a key predictor of poststroke language impairment in BWA. These findings have important implications for the assessment and diagnosis of aphasia in bilingual individuals.